Dental morphology of Microtus (Terricola) voles from Calabria (Southern Italy) and relationships with M. (T.) savii (Rodentia, Arvicolidae) - Armando Nappi (Hystrix, the Italian Journal of Mammalogy, 2005)
Abstract Microtus (Terricola) savii brachycercus (von Lehmann, 1961) was described as a Calabrian endemism. More recently, by chromosome evidence, it was considered as a valid species. Comparison of the first lower molar morphometry between Calabrian Terricola and M. savii populations show small differences. This may be explained by a recent separation of the two groups. Biogeographical, geographical and paleogeographical features of the Calabria, are also showed in order to understand a possible role in ground vole differentiation. Riassunto Morfologia dentaria delle arvicole Microtus (Terricola) della Calabria (Sud Italia) e relazioni con M. (T.) savii (Rodentia, Arvicolidae) Microtus (Terricola) savii brachycercus (von Lehmann, 1961) fu descritto come un endemismo calabro. Più recentemente, da evidenze cromosomiche, è stato considerato buona specie. Analisi comparative sulla morfometria del primo molare inferiore tra Terricola calabresi e popolazioni di M. savii mostrano piccole differenze. Ciò può essere spiegato da una segregazione recente dei due gruppi. Sono altresì illustrate le caratteristiche biogeografiche, geografiche e paleogeografiche della Calabria per comprendere un possibile ruolo nella differenziazione delle arvicole sotterranee.